Isolation of Pathogenic Organisms from Suya Meat Obtained from Selected Local Governments in Ogun East Senatorial District of Ogun State, Nigeria - Z. M, Oladunjoye; J. A, Quadri; M. A, Ojure; O. S, Usiobeigbe (International Research in Medical and Health Sciences, 2019)
This study was carried out to isolate salmonella typhi from suya meat sold within Ijebu-Ode and Ijebu North East Local Government Areas of Ogun State. Twenty skewers of suya meat were obtained randomly from suya vendor at popular suya spots (10 spots) in Ijebu-Ode and Ijebu North East Local Government areas. The samples were immediately wrapped in sterile aluminum foil to prevent contamination and then transported to the laboratory for microbial analysis without delay. The samples were cultured on MacConkey and SSA as well as peptone water. The result was analysed using Spss 20.0 at p > 0.5. Organisms such as Salmonella spp., E. coli, and Klebsiella were the organisms isolated from suya obtained at the two local government areas with little variations in the type of organisms isolated in the suya in different areas. Based on the outcome of this study, it was recommended that government should set up a committee to monitor suya processing and also create an association under which all suya sellers will be registered to ensure safe condition for processing in other to prevent harboring of various organisms that cause diseases and are harmful to the health of man.